Article RETRACTED due to manipulation by the authors and citations Physical activity levels among Malaysian University and State University of Medan Students: gender difference and the influence of BMI - Imran Akhmad; Zulfan Heri; Hariadi Hariadi; Nurkadri Nurkadri; Novita Novita; Syed Kamaruzaman Syed Ali; Mohd Faisal Mohamed; Wail Muin Ismail; Vishalache A/P Balakrishnan; Satria Yudi Gontara; Hendra Setyawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The decline in physical activity has adversely impacted physical health, with university students being particularly affected. Thus, this study examined the effect of gender and Body Mass Index (BMI) on physical activity levels among Malaysian universities and Medan State University students. The research involved 130 students from education universities in Malaysia and Medan State Universities. The data were collected using the Physical Activity Questionnaire for Adolescents (PAQ-A). The study indicated significant differences in physical activity levels among university students. This difference might be affected by gender, with male students showing significantly higher physical activity levels than female students (Sig. = 0.001 and η² = 0.082). Therefore, it is important for universities to consider such factors in designing health and wellness programs, especially to increase female students' participation in physical activity. Nonetheless, the statistical test showed no significant difference was found in physical activity levels among the different Body Mass Index (BMI) categories. This finding indicates that, unlike gender, BMI does not significantly affect the physical activity levels of university students (Sig. = 0.310). The implications of these findings suggest an urgent need for tailored health interventions in university settings, particularly Medan State University. The university can create an environment that supports active lifestyles and contributes significantly to improving students' health and well-being by providing accessible sports facilities, organizing fitness classes, and promoting active transportation options. This strategy is expected to address the challenges of participation in physical activity, particularly among female students, thereby increasing awareness and participation in overall physical activity.